CONFIRMATION OF A SULFUR-RICH LAYER ON PYRITE AFTER OXIDATIVE DISSOLUTION BY FE(III) IONS AROUND PH 2 - Sasaki K.; Tsunekawa M.; Ohtsuka T.; Konno H. (My University, 1997)
The stoichiometry of pyrite dissolution by Fe(II) ions was studied in chloride media around pH 2. Pyrite was found to dissolve nonstoichiometrically during the initial tens of hours and a S-rich layer was formed on the pyrite due to preferential dissolution of iron. The major constituent of the layer was elemental S, identified by X-ray photoelectron spectroscopy (XPS) and Raman spectroscopy.